Examination of age-related core stability and dynamic balance in hockey players - Kokinda, M.; Jesensky, M.; Kandrac, R.; Kicura, D.; Turek, M.; Chovanova, E. (SportMont, 2018)
The purpose of the study was to assess core stability and to determine age-related differences in the unilaterality of limb movements in hockey players. The sample included 152 hockey players aged 12 to 35 years. Every player performed the upper quarter and the lower quarter Y-balance tests. Performances of players showed high degree of individuality, which was expressed as the composite score. The difference greater than 4 cm in movements performed by a left or right limb indicates imbalance and higher risk of injury. Of 152 players, 27 and 26 players showed a difference higher than 4 cm for the lower quarter and the upper quarter, respectively. Of all age categories, 61% of senior players showed muscle imbalance. This may have been caused by factors present at school age because 52% of U13 players showed imbalance. We conducted statistical analysis to determine differences for each of the directions in relation to limb length. The cross-sectional data have shown non significant differences between age categories studied. For the development of ice hockey players, it is important to eliminate movement imbalance. The results have shown that the category at risk includes the U13 players, who may suffer from movement imbalance in the senior category.